VARIABILIDADE DOS ATRIBUTOS FÍSICO - Uhde, Leonir T.; Pereira, Pablo d. F.; Battaglin, Raquel F.; Sartori, Cesar O.; Maixner, Adriano R.; Fernandes, Sandra B. V.; Berto, Jorge L. (Salão do Conhecimento, 2013)
Resumo